Exploring spatio-temporal change in global land cover using categorical intensity analysis - Lamchin, Munkhnasan; Bilintoh, Thomas Mumuni; Lee, Woo-Kyun; Ochir, Altansukh; Lim, Chul-Hee (Frontiers in Forests and Global Change, 2022)
Abstract: During the twenty-first century, the rate of land degradation and urbanization around the world has increased significantly. Herein, the spatio-temporal changes in global land cover are evaluated according to continental and climatic zone via categorical intensity analysis of the European Space Agency’s climate change initiative (ESA-CCI) data for the period 1992 to 2018. Specifically, the decrease, increase, and expansion processes of the land cover are calculated on a global scale across continents and climates at the category level for five time intervals, namely 1992-1997, 1997-2002, 2002-2007 and 2007-2012, 2012-2018. The following six land categories are assessed: Cropland, Forest, SGO (Shrubland, Grassland, and Other), Urban, Bare areas, and WIS (Water, ice, and snow). After accuracy assessment, the global land-cover map for 2009 from the GlobCover data is selected, and a reclassified version of this map is used as a verification tool for comparison with the reclassified study data. The analysis of changes over the last 26 years shows that the loss intensities for Cropland are dormant during the first and second time intervals, but active during the third, fourth, and fifth time intervals. By contrast, Forest experiences loss intensities during all time intervals, and SGO experiences active loss only during the second time interval. Urban is the only category that experiences active gain intensities during all time intervals. The present study also indicates that, for the last 26 years, urbanization has degraded and converted the land in temperate regions. Additionally, in South America and tropical regions, the expansion of Cropland is the biggest contributor to the decline in Forests and SGO.